2022
DOI: 10.3390/met12091483
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Replacing Coke with Biomass Fuel on Sinter Properties and Pollutant Emissions

Abstract: In the iron-ore-sintering process, the use of biomass charcoal instead of coke breeze can reduce the emission of flue gas pollutants and alleviate the energy crisis of fossil fuels. However, the direct application of biomass charcoal to iron ore sintering is bound to affect the sinter properties. The effects of biomass charcoal addition on the sintering ore properties and flue gas pollutants emission were studied through sintering cup and related performance test experiments. Meanwhile, the influence mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…20 During the sintering process of iron ore, when the substitution ratio of biocarbon for coke fines is 50%, the emission of NO during sintering is minimized, with a reduction of over 90% in accumulated NO emissions in the exhaust gas. Chao Liu et al 21 suggested that the optimal addition ratio of biomass charcoal is 40%, under which conditions NO x is reduced by 25.7%. Regarding the decrease in oxygen content and the increase in oxygen consumption, elemental analysis reveals that poplar wood charcoal has higher fixed carbon and hydrogen content compared to coke fines.…”
Section: Results and Analysismentioning
confidence: 99%
“…20 During the sintering process of iron ore, when the substitution ratio of biocarbon for coke fines is 50%, the emission of NO during sintering is minimized, with a reduction of over 90% in accumulated NO emissions in the exhaust gas. Chao Liu et al 21 suggested that the optimal addition ratio of biomass charcoal is 40%, under which conditions NO x is reduced by 25.7%. Regarding the decrease in oxygen content and the increase in oxygen consumption, elemental analysis reveals that poplar wood charcoal has higher fixed carbon and hydrogen content compared to coke fines.…”
Section: Results and Analysismentioning
confidence: 99%
“…Most of the atmospheric pollutants released come from the iron and steel industry, and more than 42% of the dust, 65% of the SO 2 , and 55% of the NO x are emitted as exhaust gas pollutants during the sintering process. The S and N content in fossil fuels is high and a large amount of SO 2 and NO x is released during iron ore sintering [3,4].…”
Section: Introductionmentioning
confidence: 99%